INVESTIGATING THE ASSOCIATIONS BETWEEN CARDIORESPIRATORY FITNESS, SLEEP AND COGNITION IN AGING. - Kuhn, Tara (My University, 2020)
With increasing age there is a decline in cognitive functions, including episodic memory and executive functioning. This decline is thought to be related to changes in sleep, as sleep quality and quantity also decline with aging. Physical activity is a promising tool that has been found to increase both sleep and cognition in older adults. Physical activity has been shown to protect executive functions against poor sleep in older adults. However, it is unknown if physical activity also helps to protect memory against poor sleep, and if this relationship differs by age. The present study investigated the relationship between cardiorespiratory fitness, sleep, and memory in both older and young adults. Twenty-six older adults (M ± SD: 70.7 ± 2.8) and thirty-five young adults (M ± SD: 21.0 ± 3.1) completed the Rockport 1-mile walk test to measure cardiorespiratory fitness. Participants wore an actigraph for one week to measure habitual sleep, and returned for a second visit to perform tasks assessing episodic memory and executive functioning. An interaction was found between sleep quality and cardiorespiratory fitness (p = .021), in that sleep enhanced memory for low fit older adults (p = .047) but not for high fit older adults (p = .19). Sleep also predicted executive functioning performance in older adults (p = .007), but this association was observed regardless of cardiorespiratory fitness. No significant relationships were observed between cardiorespiratory fitness, sleep, and cognition in young adults. Overall, these results suggest the relationship between cardiorespiratory fitness and sleep may differ for episodic memory and executive functions. Given that these aspects of cognition are supported by different underlying neurological processes, fitness and sleep may provide complementary support for the aging brain. Future research should further investigate the underlying mechanism for the relationship between sleep, cardiorespiratory fitness, and cognition.
Keywords: Sleep; Exercise; Cognition; Memory